Geometrical Knowledge and Geometrical Self-efficacy among Abused and Neglected Kindergarten Children - Tirosh, Dina; Tsamir, Pessia; Tabach, Michal; Levenson, Esther; Barkai, Ruthi (Scientia in educatione, 2013)
The aim of this study is to investigate the geometrical knowledge as well as the geometrical self-efficacy of kindergarten children, including abused and neglected kindergarten children. Individual interviews were conducted with 141 kindergarten children, ages 5-6 years old, of which 69 children were labeled as abused and neglected by the social welfare department of their municipality. Results indicated that both groups of kindergarten children had high self-efficacy beliefs related to identifying geometrical figures which were not significantly related to knowledge. In addition, significant differences in knowledge were found between the two groups.